1994
DOI: 10.1111/j.1365-2885.1994.tb00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and pharmacokinetics of metoclopramide in cattle

Abstract: The bioavailability of metoclopramide was investigated in three steers following administration of 8 mg/kg by the oral, abomasal (cannula), and intravenous routes, using a Latin square design. The mean (+/- SD) oral and abomasal bioavailabilities were 51.3 +/- 30.7% and 76.2 +/- 15.5%, respectively. The mean value for clearance (Cl) was 20.1 +/- 5.9 ml/min and the volume of distribution (Vd) was 0.51 +/- 0.19 l/kg. Additional pharmacokinetic parameters for metoclopramide were determined following intravenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
4
9
0
Order By: Relevance
“…It is suggested that metoclopramide at 0.3 mg/kg could produce mild and transient prokinetic effect. This finding supports the result of Jones et al (1994) that recorded short half-life of metoclopramide and suggested use continuous release device to produce prolonged effect. Metoclopramide is an antagonist at dopaminergic (D2) receptors and a serotonin (5-hydroxytryptamine; 5-HT) agonist at 5-HT4 receptors and antagonist at 5-HT3 receptors (Plaza et al 1996).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is suggested that metoclopramide at 0.3 mg/kg could produce mild and transient prokinetic effect. This finding supports the result of Jones et al (1994) that recorded short half-life of metoclopramide and suggested use continuous release device to produce prolonged effect. Metoclopramide is an antagonist at dopaminergic (D2) receptors and a serotonin (5-hydroxytryptamine; 5-HT) agonist at 5-HT4 receptors and antagonist at 5-HT3 receptors (Plaza et al 1996).…”
Section: Discussionsupporting
confidence: 93%
“…Similar finding was recorded in goat by Huhn et al (1992) and Huhn and Nelson (1997) who found that a biological half-life of metoclopramide was 0.62 h and the serum concentrations following IM administration of 0.5 mg/kg rose rapidly to a peak of 160.9 ng/ml at 15 min post-dosing and then declined in parallel with the elimination phase of the IV. The effect of the drug lasted for short period and the recorded changes disappeared at 40 minutes suggesting its effect is transient, the finding, which support the previous results that conclude the short half-life, and low minimum pharmacologically effective concentration, and rapid clearance for metoclopramide in cattle (Jones et al 1994). It is suggested that metoclopramide at 0.3 mg/kg could produce mild and transient prokinetic effect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…28 Another source reports the BA of oral metoclopramide to be about 75%, but varying between approx 30% and 100%. 14 Other sources report values of 51% (standard deviation: 31%), 40 32-97%, 41 77%, 42 and 68% (standard deviation: 13%). 43 This wide range in BA has been attributed to the interindividual variable first-pass effect.…”
Section: Pharmacokinetic Properties Absorption and Permeabilitymentioning
confidence: 99%
“…The synthetic scheme and structures of metoclopramide and some synthesized metabolites are shown in Figure LA-F. The bioavailability and pharmacokinetic parameters of metoclopramide have been investigated in steers and cows (Jones et aL, 1993) using an HPLC assay (Jones and Bowen, 1991). Previous studies have identified eight metabolites in the rat, four in the dog, and three in human urine, with 2-[(4-amino-5-chloro-2-methoxybenzoyl)amino]acetic acid being the only common metabolite (Bakke and Segura, 1976;Teng et al, 1977).…”
mentioning
confidence: 99%